Parametric study of various configurations for thermally hybrid gas turbine-integrated desalination system - Seyyed Ehsan Shakib; Amirhossein Joveini; Mohammad Derayatifar (Results in Engineering, 2025)
If water shortage calls for a solution, hybrid desalination systems, resorting to thermal and membrane processes, are one of the best answers. The paper studies a novel hybrid system: MED-TVC with RO, using the waste heat from the gas turbine cycle as its feed source. Four different configurations of the system were thus evaluated by means of a detailed thermodynamic and thermoeconomic model. Among the operating parameters adjusted using GA were the number of effects in MED-TVC. The results indicate that increasing the number of MED-TVC effects intensifies freshwater production up to 157 % and increases exergy efficiency. Among the configurations, Configuration 2 consistently achieved the highest freshwater production (up to 180,000 m³/day), significant cost reduction (from $1.29 to $0.93/m³), and strong resilience to variations in operating conditions. These findings establish Configuration 2 as the most effective design. This research provides a practical framework for optimizing hybrid desalination systems, promoting their role in sustainable and cost-efficient freshwater generation.